Efektifitas Media Whatsapp Group Dalam Pembelajaran Pendidikan Agama Islam (PAI) di SMA Kabupaten Batang Pada Masa Pandemi Covid-19 - Wirani Atqia; Bahrul Latif (STAI Bumi Silampari, 2021)
This study aims to determine the effectiveness of using Whatsapp group media in learning Islamic religious education carried out in SMA. This study uses descriptive qualitative research where the data obtained are described in the form of descriptive sentences. This study uses the method of observation, interviews and documentation. The results of interviews conducted using Google Forms show that learning Islamic religious education using WhatsApp group media during the COVID-19 pandemic is effective. Islamic religious education learning using whatsapp group media has a weakness where students are not active in the teaching and learning process and learning using this media has advantages such as easy to send files, easy to use and others.